2022
DOI: 10.3390/app12115756
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary and Mandibular Third Molars Impaction with Associated Pathologies in a North Cyprus Population: A Retrospective Study

Abstract: This study aimed to find out the incidence of impacted third molars and associated pathologies in people who live in the North Cyprus population. Dr. Burhan Nalbantoglu State Hospital is the only hospital that has an oral and maxillofacial surgery department among the state hospitals in North Cyprus. Patients who were referred to this department during a one-year period due to the complaints regarding their third molar were included in our study. This retrospective study involved 550 patients aged 16 to 65 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A number of studies found that the prevalence of impacted third molars was higher in the mandible [28]. There is still debate about whether the impaction of the mandibular third molar or maxillary third molar is more commonly seen [33]. It is generally agreed that the mandibular third molar becomes impacted more than any other tooth; from 17% to 25% of the general population will have one or more impacted third molars [34].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies found that the prevalence of impacted third molars was higher in the mandible [28]. There is still debate about whether the impaction of the mandibular third molar or maxillary third molar is more commonly seen [33]. It is generally agreed that the mandibular third molar becomes impacted more than any other tooth; from 17% to 25% of the general population will have one or more impacted third molars [34].…”
Section: Discussionmentioning
confidence: 99%
“…After the maxillary and mandibular third molars, the maxillary canines are the third most impacted teeth, 1 and there are more palatally impacted maxillary canines than labially impacted maxillary canines. Moreover, maxillary canines are more commonly impacted than mandibular canines.…”
Section: Introductionmentioning
confidence: 99%
“…A tooth is said to be impacted when it fails to erupt more than a year after its expected eruption time. 3,[6][7][8][9] Although most impacted teeth are asymptomatic, impacted third molars are still a significant clinical problem because untreated impacted third molars can cause a number of complications, including pericoronitis, periodontitis, caries, root resorption of adjacent teeth, temporomandibular joint disorders, bone loss, development of odontogenic cysts, and tumors of the oral cavity. 2,4,9 Third molar pain and edema are another group of problems that call for urgent dental care during the COVID-19 pandemic.…”
mentioning
confidence: 99%